Difference of Procalcitonin Levels in Gram-Positive and Gram-Negative Bacterial Sepsis Patients of Indonesia Army Central Hospital Gatot Soebroto in 2016 - Nindy Handayani; Soroy Lardo; Nunuk Nugrohowati (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2022)
Introduction: Procalcitonin is known as a marker of infection and indicator for severity of infections. In sepsis, elevated procalcitonin levels in blood have a significant value that can be used as a sepsis biomarker. The aim of this study was to determine the mean difference of procalcitonin levels in Gram-positive and Gram-negative bacterial sepsis patients.Methods: This study used quantitative method with cross sectional approach. The sample of this study were bacterial sepsis patients of Indonesia Army Central Hospital Gatot Soebroto in 2016 which were divided into two groups: Gram-positive and Gram-negative bacterial sepsis patients with the number of each group was 30 samples. The data were analyzed by using independent t test.Results: This study showed that mean levels of procalcitonin in Gram-positive bacterial sepsis patients was 6.47 ng/ml and Gram-negative was 66.04 ng/ml. There was a significant difference between mean levels of procalcitonin in Gram-positive and Gram-negative bacterial sepsis patients of Indonesia Army Central Hospital Gatot Soebroto in 2016 with p value = 0.000 (p < 0.05).Conclusion: The mean difference of procalcitonin levels in Gram-negative bacterial sepsis patients were higher than Gram-positive bacterial sepsis patients, because Gram-negative bacteria have lipopolysaccharide which is a strong immunostimulator and increases TNF-α production higher than Gram-positive bacteria.